TOWARDS THE FUTURE: DIGITAL TRANSFORMATION IN INDONESIAN BANKING AND ITS IMPLICATIONS FOR ECONOMIC GROWTH AND PUBLICPROSPERITY - Hermiyetti Hermiyetti (CV. Adiba Aisha Amira, 2025)
Digital transformation has emerged as a pivotal force reshaping the Indonesian banking sector, with profound implications for economic growth and public prosperity. This paper comprehensively analyzes the trends, challenges, and opportunities associated with digital transformation in Indonesian banking. By examining the adoption of digital channels, fintech innovations, and regulatory frameworks, this study highlights the transformative impact of digitalization on traditional banking practices and customer interactions. Additionally, it explores the Role of regulatory bodies in fostering a conducive environment for digital financial services and promoting financial inclusion. The findings underscore the potential of digital transformation to drive economic growth, enhance operational efficiency, and extend banking services to underserved populations. However, challenges such as cybersecurity risks, regulatory compliance issues, and talent shortages must be addressed to realize the full benefits of digitalization. By prioritizing cybersecurity measures, fostering innovation, and investing in talent development, Indonesian banks can navigate the complexities of the digital age and contribute to sustainable economic development and public prosperity.